The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1097/00005344-200209000-00017
|View full text |Cite
|
Sign up to set email alerts
|

NG-Nitro-l-Arginine Methyl Ester–Induced Hypertension and Natriuretic Peptide Gene Expression: Inhibition by Angiotensin II Type 1 Receptor Antagonism

Abstract: This study examined the role of angiotensin II in the increase of blood pressure, activation of cardiac natriuretic peptide gene expression, left ventricular hypertrophy, and vascular changes in nitric oxide-deficient hypertension. N(G)-nitro->L-arginine methyl ester (>L-NAME, 20 mg/kg/d), angiotensin II type 1 receptor (AT ) antagonist losartan (20 mg/kg/d), or their combination were administered orally for 8 weeks in Wistar rats. >L-NAME elevated systolic blood pressure, which reached its maximum within 4 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…34 It is of note that in experimental NO-deficient hypertension, AT 1 receptor blockade reduced blood pressure and cardiac load, but the mesenteric resistance vessels still showed an inward hypertrophic response. 17 The present results show that the effect of renal failure on resistance vessel structure and the correction of these changes by losartan can be dissociated from the level of blood pressure.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…34 It is of note that in experimental NO-deficient hypertension, AT 1 receptor blockade reduced blood pressure and cardiac load, but the mesenteric resistance vessels still showed an inward hypertrophic response. 17 The present results show that the effect of renal failure on resistance vessel structure and the correction of these changes by losartan can be dissociated from the level of blood pressure.…”
Section: Discussionmentioning
confidence: 52%
“…18 For endothelium-independent relaxation, the endothelium was removed by perfusing air through the lumen. Morphology of small arteries was examined with a pressure myograph (Living Systems Instrumentation Inc), as previously reported, 17 and the development of myogenic tone was inhibited by Ca 2ϩ -free solution containing 30 mmol/L EDTA. 19 …”
Section: Mesenteric Arterial Responses and Morphology In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we observed that Ang II infusion markedly downregulated iNOS mRNA levels in fatty acidsupplemented groups compared with the standard diet group. As nitric oxide attenuates ventricular natriuretic peptide expression (28), Ang II-induced inhibition of nitric oxide synthesis may contribute to the upregulation of ANP and BNP gene expression in the rat heart.…”
Section: Discussionmentioning
confidence: 99%
“…Morphology of small arteries was examined with a pressure myograph (Living Systems Instrumentation; Burlington, VT) as previously reported, and the development of myogenic tone was inhibited by Ca 2ϩ -free solution containing 30 mmol/l EDTA (30). Three 5-m aortic cross sections from the 18 rats that were followed for another 8 wk were stained with von Kossa stain and processed for light microscopic evaluation.…”
Section: Methodsmentioning
confidence: 99%